Analysis of Elementary School Students' Ability at Sd Inpres Sailong in Performing Overhand Pass and Underhand Pass in Volleyball - Nuramalia Anugrah; Muhammad A. Fadhil Akbar Mappajonga; Muhammad Kadafi Taruna; Syahrul Asyir; Muh. Yusril S.; Mohammad Mursyid Dhziaulhaq (CV Lentera Cendekia Indonesia, 2025)
Introduction. Physical education at the elementary school level, one of the sports is volleyball. Overhead passing and underhand passing are important basic skills mastered by students. However, initial observations at SD Inpres Sailong showed that students were still able to apply both techniques with variations and perhaps not optimally. The purpose of this study was to see how well students' abilities were in performing overhand and underhand passing when playing volleyball. Method. In this study, a quantitative descriptive approach was applied to a sample of 12 students in grade VI at SD Inpres Sailong. The tool used was a one-minute overhand and underhand passing skill test. The average score and percentage of student ability categories were calculated using descriptive statistics. Results. The average underhand passing ability was 21.67 with a fairly good category, where 50% of students were in the good category. The average overhand passing ability was 24.83 with a good category, where 75% of students were in the good category. In general, students were more proficient in overhand passing than underhand passing. Conclusion. Students at SD Inpres Sailong have good overhand passing and fairly good underhand passing abilities. In order for students' basic volleyball technical abilities to develop in a balanced manner, more intensive training is needed in underhand passing techniques.